2017
DOI: 10.1557/jmr.2017.58
|View full text |Cite
|
Sign up to set email alerts
|

Pushing the detection limit of thin film magnetoelectric heterostructures

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
36
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(36 citation statements)
references
References 42 publications
0
36
0
Order By: Relevance
“…Magnetoelectric laminate composites feature high sensitivity towards change in magnetic fields (AC magnetic fields), as well as (1) e = 0 +Δ compact size, low-cost and room temperature operation. Therefore, the ME sensors are ideal candidate for the biomagnetic liver susceptometry (Fang et al, 2009;Freeman et al, 2017;Gillette et al, 2011;Lage et al, 2012;Li, Zhao, Zhang, & Datta, 2010;Li et al, 2013;Lu et al, 2015;Ramesh & Spaldin, 2007;Röbisch et al, 2017;Xu et al, 2018).…”
Section: Enhan Cing the S En S Itivit Y And S I G Nal-to -Nois E R mentioning
confidence: 99%
“…Magnetoelectric laminate composites feature high sensitivity towards change in magnetic fields (AC magnetic fields), as well as (1) e = 0 +Δ compact size, low-cost and room temperature operation. Therefore, the ME sensors are ideal candidate for the biomagnetic liver susceptometry (Fang et al, 2009;Freeman et al, 2017;Gillette et al, 2011;Lage et al, 2012;Li, Zhao, Zhang, & Datta, 2010;Li et al, 2013;Lu et al, 2015;Ramesh & Spaldin, 2007;Röbisch et al, 2017;Xu et al, 2018).…”
Section: Enhan Cing the S En S Itivit Y And S I G Nal-to -Nois E R mentioning
confidence: 99%
“…[9][10][11][12][13] The results have encouraged investigations to enable the detection of weak low frequency biomagnetic fields with room temperature sensors. 14 This has involved research to increase the effect size of the ME response, e.g., materials, effects of device geometry and operation modes, [15][16][17][18] resonance-enhancement and loss mechanisms, 13 and investigation of noise effects and their behavior including the Johnson-Nyquist noise [19][20][21][22][23] from dielectric losses in piezoelectric materials 24 in ME cantilevers and electronics, noise in magnetostrictive (MS) materials, and thermal vibration noise. 23,[25][26][27][28] Different operation modes investigated for low frequency biomagnetic field sensing 14 include (1) direct detection, where magnetic fields oscillating at the cantilever resonance directly excite magnetostrictivepiezoelectric strain coupling and resonance-enhanced signals; (2) modulation techniques, [29][30][31] where signal fields are detected as sidebands to a carrier as a result of frequency mixing in non-linear functional materials; and (3) the ΔE effect, 32,33 where the field dependence of the elastic modulus in magnetostrictive materials is used.…”
Section: Introductionmentioning
confidence: 99%
“…It also has the advantages of low cost, light weight, easy fabrication, and high magnetic directivity. [16,19,[27][28][29][30][31][32] However, the system-level application based on the ME sensor is still in an early stage, although some prototypes have been developed for different usage scenarios. Recently, Chu et al have reported a (1-1) type ME sensor with a 1D configuration.…”
Section: Introductionmentioning
confidence: 99%